Systematization of Cost Factors for Cost Management at Industrial Enterprises - Radionova, N. Y. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
Identification and structuring o f factors determining the cost level has significant importance in cost analysis and control. Cost factors need to be systematizedfor more effective cost management. The objective o f the study is to identify and structure the factors with impact on the enterprise costs. The external and internal factors with impact on the enterprise costs in industry are highlighted. For cost management purposes, it is proposed to group the cost factors into the two categories: structural and functional. The essence of structural andfunctionalfactors is shown; a classification o f functionalfactors is given. The ejfect o f a structural factor such as products range (complexity) is illustrated. As the factor o f complexity, combined with cost analysis systems and innovative tools o f analysis (ABC and XYZ methods), has been increasingly in focus o f analysts, three problems are described which, once dealt with, will enable ABC method to fit into the cost management system. The importance o f another structural factor o f costs, technology selection, in cost management is shown. The analysis allows fo r the following conclusions: for purposes ofcurrent cost management, including one based on operational analysis, the output needs to be addressed as the central factor determining the cost level; in the strategic perspective, an enterprise needs to concentrate on calculating the costs for the structural alternatives that are supposed to determine its competitive position; for cost management purposes, the costfactors should be broken into two categories, structural andfunctional; a specific management system exists for each cost factor, which is greatly important for the positioning of an enterprise.